Hak-Hak Perempuan dan Anak dalam Hukum Keluarga Islam di Aceh: Analisis Kritis melalui Maqāṣid al-Syarī‘ah dan Pluralisme Hukum - Maimun Abdurrahman Amin; Zaki Satria; Fakhrul Rijal (Pascasarjana UIN ANTASARI Banjarmasin, 2026)
The implementation of the Qanun in Aceh still faces fundamental problems in the form of a gap between the legal text and the reality in society. Conservative religious interpretations and limited understanding of law enforcement officials can result in suboptimal protection of women's and children's rights in Islamic family law. This study aims to analyze the role of the Qanun in strengthening women's and children's rights in Islamic family law in Aceh. This study uses a literature study approach. The data analysis stage was carried out using qualitative content analysis and critical analysis techniques. The results of the study indicate that: 1). The historical dynamics of the Islamic family Qanun and responses to gender issues in Aceh indicate that the development of the Islamic Family Qanun in Aceh demonstrates a complex dialectic between Islamic values, local wisdom, and global awareness of gender equality. The post-2004 tsunami was a crucial momentum where the Qanun underwent progressive reforms despite still facing resistance from conservative religious understandings. 2). Protection of women's rights in the Aceh Qanun: between progress and challenges is that Qanun No. 6 of 2021 represents substantive progress in the protection of women's rights, particularly in marriage and divorce. However, its implementation is still hampered by patriarchal culture, the capacity of the apparatus, and the gender-biased interpretation of classical fiqh. 3). The effectiveness of the Qanun in Protecting Children's Rights and Ensuring the Best Interests of Children is that the Qanun has adopted the principle of the best interests of the child comprehensively, but its effectiveness is limited by the capacity of judges in child psychology, coordination between institutions, and a lack of synchronization with the national child protection system. Implementation of the findings of this study requires three strategic steps: massive socialization, increasing the capacity of Sharia Court judges, and harmonizing the Aceh Qanun with the national legal system.